Cumulative cancer incidence and mortality after kidney transplantation in Japan: A long‐term multicenter cohort study. (13th December 2020) - Imamura, Ryoichi; Nakazawa, Shigeaki; Yamanaka, Kazuaki; Kakuta, Yoichi; Tsutahara, Koichi; Taniguchi, Ayumu; Kawamura, Masataka; Kato, Taigo; Abe, Toyofumi; Uemura, Motohide; Takao, Tetsuya; Kishikawa, Hidefumi; et al.
Abstract: Kidney transplantation is the most promising treatment to improve mortality and life quality in end‐stage kidney disease; however, cancer remains a leading cause of death. Several factors including immunosuppressants might be associated with a gradual increase in cumulative cancer incidence after kidney transplantation. Risk factors for cancer and overall and cancer‐specific survival were analyzed in 1973 kidney transplant recipients from three study institutions in Japan. The 5‐, 10‐, 20‐, and 30‐year overall and cancer‐specific survival rates were 93.3%, 88.4%, 78.0%, and 63.6% and 99.4%, 98.0%, 95.3%, and 91.7%, respectively. The overall survival rate was significantly higher and the graft survival rate was significantly lower in recipients without cancer than in those with cancer. Older recipient age, longer dialysis duration before kidney transplantation, and history of transfusion were significant predictors of cancer. Dialysis duration before kidney transplantation was a prognostic factor of overall survival rate. Regarding cancer‐specific survival rates, older recipient age and dialysis duration before kidney transplantation were prognostic factors of worse cancer‐specific survival rates. The type of immunosuppressant was not associated with an increased cancer rate. Aggressiveness of immunosuppressant regimens or potent immunosuppressants might improve graft survival rate while inducing de novo cancer after kidney transplantation. Older age and longer dialysis duration before kidney transplantation were risk factors of cancer‐specific survival rate. Abstract : Overall patient survival rate was significantly higher in patients without cancer, whereas graft survival rate was significantly higher in those with cancer. The aggressiveness of immunosuppressant regimens or potent immunosuppressant use after kidney transplantation improved graft survival rate, while increasing cancer morbidity. The type of immunosuppressant was not associated with increased cancer morbidity.